A late-Holocene multiproxy fire record from a tropical savanna, eastern Arnhem Land, Northern Territory, Australia. (May 2021) - Rehn, Emma; Rowe, Cassandra; Ulm, Sean; Woodward, Craig; Bird, Michael
Fire has a long history in Australia and is a key driver of vegetation dynamics in the tropical savanna ecosystems that cover one quarter of the country. Fire reconstructions are required to understand ecosystem dynamics over the long term but these data are lacking for the extensive savannas of northern Australia. This paper presents a multiproxy palaeofire record for Marura sinkhole in eastern Arnhem Land, Northern Territory, Australia. The record is constructed by combining optical methods (counts and morphology of macroscopic and microscopic charcoal particles) and chemical methods (quantification of abundance and stable isotope composition of pyrogenic carbon by hydrogen pyrolysis). This novel combination of measurements enables the generation of a record of relative fire intensity to investigate the interplay between natural and anthropogenic influences. The Marura palaeofire record comprises three main phases: 4600–2800 cal BP, 2800–900 cal BP and 900 cal BP to present. Highest fire incidence occurs at 4600–4000 cal BP, coinciding with regional records of high effective precipitation, and all fire proxies decline from that time to the present. 2800–900 cal BP is characterised by variable fire intensities and aligns with archaeological evidence of occupation at nearby Blue Mud Bay. All fire proxies decline significantly after 900 cal BP. The combination of charcoal and pyrogenic carbon measures is a promising proxy for relative fire intensity in sedimentary records and a useful tool for investigating potential anthropogenic fire regimes.